2017
DOI: 10.1016/j.kjms.2017.05.002
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cranioplasty in cognitive and functional improvement: Experience of post traumatic brain injury inpatient rehabilitation

Abstract: To investigate the effect of cranioplasty on rehabilitation of post-traumatic brain injury (TBI) patients, 37 patients with TBI were arranged by retrospectively assessment study. Those TBI patients receiving in-hospital rehabilitation in the Department of Rehabilitation in a medical center of South Taiwan from 2010 to 2015 were assigned into two groups: A and B. All patients entered the multidisciplinary holistic in-patient rehabilitation training for about 1 month. Patients in Group A received decompressive c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 30 publications
1
11
1
1
Order By: Relevance
“…However, neurorehabilitation programs (if performed) might affect outcomes after longer times (Jolliffe, Lannin, Cadilhac, & Hoffmann, 2018), reinforcing cranioplasty effects on spontaneous cognitive recovery. Su et al (2017) observed synergetic effects of cranioplasty on TBI patients with rehabilitation training, both in the motor and in the cognitive domains.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…However, neurorehabilitation programs (if performed) might affect outcomes after longer times (Jolliffe, Lannin, Cadilhac, & Hoffmann, 2018), reinforcing cranioplasty effects on spontaneous cognitive recovery. Su et al (2017) observed synergetic effects of cranioplasty on TBI patients with rehabilitation training, both in the motor and in the cognitive domains.…”
Section: Discussionmentioning
confidence: 89%
“…After reading them, one article was excluded because reported duplicate patients (Honeybul, Janzen, Kruger, & Ho, ), who were included in a more recent and larger simple size study (Honeybul, Janzen, Kruger, & Ho, ), whereas two articles were excluded for inadequate study design (Huang et al, ; Liang et al, ). Although we contacted eight authors for further information regarding missing data (Bender et al, ; Di Stefano et al, ; Honeybul et al, ; Jasey, Ward, Lequerica, & Chiaravalloti, ; Shahid, Mohanty, Singla, Mittal, & Gupta, ; Songara, Gupta, Jain, Rege, & Masand, ; Stelling, Graham, & Mitchell, ; Su et al, ), only four of them were able to provide original individual data useful for our meta‐analysis (Di Stefano et al, ; Honeybul et al, ; Jasey et al, ; Songara et al, ). At the end of selection, six articles and two systematic reviews (Malcolm et al, ; Xu et al, ) have been included in the present study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Importante ressaltar que há estudiosos 61 quanto ao efeito da cranioplastia em pacientes submetidos a CD por TCE grave, que alertam que a melhoria da qualidade da atividade diária funcional e a função cognitiva são muito mais refinadas com a intervenção da cranioplastia durante a reabilitação hospitalar.…”
Section: Funcionalidadeunclassified